TELAAH ATAS LUKAS 10:25-37 DAN REVELANSINYA TERHADAP KEMANUSIAAN SETELAH PANDEMI COVID-19. - Karwayu, Andre (Universitas Katolik Parahyangan, 2021)
This article is a theological study to find the relevance of the Parable of the Good Samaritan (Luke 10:25-37) and various crucial issues posed by the COVID-19 pandemic. There are some common values of life that can be extracted from Luke 10:25-37 and the COVID-19 pandemic. These values are about living without discrimination, the practice of charity and calling to be neighbors (to be brothers to all people).These values are a challenge for the nations of the world, a global calling, and at the same time a prerequisite for realizing a new civilization, humanity after COVID-19. This simple study uses the historical-critical method and is equipped with inter-text hermeneutics method.